2021
DOI: 10.21203/rs.3.rs-48529/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors that influenced access and utilisation of sexual and reproductive health services among Ugandan youths during the COVID-19 pandemic lockdown: An online cross-sectional survey

Abstract: BackgroundThe COVID-19 pandemic has caused a wide range of disruptions in health care access in many low and middle income countries. The aim of this study was to explore factors that influenced access and utilisation of sexual and reproductive health services among Ugandan youths during the COVID-19 pandemic lockdown. MethodsThis was an online cross-sectional study carried out from April 2020 to May 2020 in Uganda. An online questionnaire was used and participants aged 18years to 30 years were recruited using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Twenty-six studies addressed impacts of COVID-19 on abortion and/or PAC in terms of demand, provision, access, or outcomes; 34 , 38–41 , 45–47 , 51 , 52 , 54 , 55 , 62 , 63 , 66 , 69 , 71–74 , 76–78 , 87–89 46% were peer-reviewed. The studies ranged widely in geographic coverage from a single town or facility to a multi-regional study covering 118 countries.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-six studies addressed impacts of COVID-19 on abortion and/or PAC in terms of demand, provision, access, or outcomes; 34 , 38–41 , 45–47 , 51 , 52 , 54 , 55 , 62 , 63 , 66 , 69 , 71–74 , 76–78 , 87–89 46% were peer-reviewed. The studies ranged widely in geographic coverage from a single town or facility to a multi-regional study covering 118 countries.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies reported on abortion-related outcomes, 34 , 38 , 55 , 62 , 66 , 69 , 71–74 , 76–78 , 87–89 seven of which covered PAC. 34 , 66 , 72 , 74 , 76 , 77 , 88 Several representative or large-scale studies reported decreases in safe abortion services during COVID-19.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations